Solitary By Any Other Name: Silence to Segregation in American Prisons - van Aken, Chelsea (2016)
This thesis examined the United States’ ability to circumvent international and constitutional law in regards to solitary confinement in American prisons. Drawing on scholarship examining inmates’ rights and inmates’ resistance movements, international human rights doctrine, United States constitutional law, activist led movements, and inmate testimony, the thesis demonstrates that the United States is able to simultaneously claim that it is meeting its human rights violations while resisting reforms to both state and federal current policy of warehousing inmates in solitary confinement for decades at a time through two strategies. First, the United States utilizes framing strategies to deny the use of solitary confinement by framing it as a necessary housing policy to guarantee safety and security within the prison. Second, the United States uses continually changing rhetoric to label solitary confinement as segregation. These two strategies allow the United States to avoid both constitutional challenges to the use of solitary confinement and meeting its obligations under international human rights agreements